Trastuzumab deruxtecan in advanced breast cancer patients with brain metastases or leptomeningeal metastases - Liu, Jinsong; Quan, Liuliu; Sang, Die; Guan, Xiao; Dou, Min; Yue, Jian; Yuan, Peng (Cancer pathogenesis and therapy, 2025)
•Trastuzumab deruxtecan showed superior intracranial overall response rate (ORR) and median progression-free survival (mPFS) than controls in both stable and active brain metastases.•DEBBRAH, TUXEDO-1, and DESTINY-Breast 12 confirm durable intracranial activity in brain metastases with trastuzumab deruxtecan.•Real-world ROSET-BM data reported median overall survival (OS, 27.0 months) and mPFS (14.6 months) in active BM, reinforcing T-DXd efficacy.•In leptomeningeal metastases (LM) cohorts, T-DXd achieved clinical benefit rate (71.4–100%), mOS (10.4–13.3 months), and mPFS (8.9–17.5 months) across studies.•For active BM, local intervention plus T-DXd (or tucatinib combination) is recommended based on efficacy stratification.